Treatment of blood blister aneurysms of the internal carotid artery with flow diversion. (24th February 2018) - Mokin, Maxim; Chinea, Angel; Primiani, Christopher T; Ren, Zeguang; Kan, Peter; Srinivasan, Visish M; Hanel, Ricardo; Aguilar-Salinas, Pedro; Turk, Aquilla S; Turner, Raymond D; Chaudry, M Imran; Ringer, Andrew J; et al.
Abstract : Background: Blood blister aneurysms (BBA) are a rare subset of intracranial aneurysms that represent a therapeutic challenge from both a surgical and endovascular perspective. Objective: To report multicenter experience with flow diversion exclusively for BBA, located at non-branching segments along the anteromedial wall of the supraclinoidal internal carotid artery (ICA). Methods: Consecutive cases of BBA located at non-branching segments along the anteromedial wall of the supraclinoidal ICA treated with flow diversion were included in the final analysis. Results: 49 patients with 51 BBA of the ICA treated with devices to achieve the flow diversion effect were identified. 43 patients with 45 BBA of the ICA were treated with the pipeline embolization device and were included in the final analysis. Angiographic follow-up data were available for 30 patients (32 aneurysms in total); 87.5% of aneurysms (28/32) showed complete obliteration, 9.4% (3/32) showed reduced filling, and 3.1% (1/32) persistent filling. There was no difference between the size of aneurysm (≤2 mm vs >2 mm) or the use of adjunct coiling and complete occlusion of the aneurysm on follow-up (P=0.354 and P=0.865, respectively). Clinical follow-up data were available for 38 of 43 patients. 68% of patients (26/38) had a good clinical outcome (modified Rankin scale score of 0–2) at 3 months. There were 7 (16%) immediate procedural and 2 (5%) delayed complications, with 1 case of fatal delayed re-rupture after the initial treatment. Conclusions: Our data support the use of a flow diversion technique as a safe and effective therapeutic modality for BBA of the supraclinoid ICA.